2015
DOI: 10.1186/s40064-015-1037-0
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacterial diversity in the phyllosphere of Amazon Paullinia cupana associated with asymptomatic and symptomatic anthracnose

Abstract: Endophytes colonize an ecological niche similar to that of phytopathogens, which make them candidate for disease suppression. Anthracnose is a disease caused by Colletotrichum spp., a phytopathogen that can infect guarana (Paullinia cupana), an important commercial crop in the Brazilian Amazon. We investigated the diversity of endophytic bacteria inhabiting the phyllosphere of asymptomatic and symptomatic anthracnose guarana plants. The PCR-denaturation gradient gel electrophoresis (PCR-DGGE) fingerprints reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 57 publications
6
27
0
Order By: Relevance
“…Similarly, bacterial diversity increased in Paullinia cupana leaves affected by anthracnose symptoms (Colletotrichum spp.) compared to leaves with no symptoms [44]. A similar tendency was detected, although not statistically significant, for bacterial communities in tomato roots attacked by the nematode Meloidogyne incognita when compared to non-infected roots [45].…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, bacterial diversity increased in Paullinia cupana leaves affected by anthracnose symptoms (Colletotrichum spp.) compared to leaves with no symptoms [44]. A similar tendency was detected, although not statistically significant, for bacterial communities in tomato roots attacked by the nematode Meloidogyne incognita when compared to non-infected roots [45].…”
Section: Discussionsupporting
confidence: 54%
“…However, plant diseases like anthracnose and oversprouting, caused by Colletotrichum guaranicola F. C. Albuq and Fusarium decemcellulare Brick, respectively, have seriously damaged P . cupana crops and limited their expansion and productivity [ 15 18 ]. There are promising alternatives for disease control–such as cultivation of resistant P .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the endophytic fungal diversity of P . cupana leaves [ 18 , 29 , 30 ] and endophytic bacterial diversity of P . cupana leaves, seeds and roots [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the AM, the disease incidence is higher than in BA, suggesting that some types of selection might be responsible for selection against Colletotrichum in AM, maintaining more antagonistic bacterial isolates in seeds. In bacterial isolated from leaves of asymptomatic and symptomatic guarana plants, was observed that symptomatic plants (with anthracnose) contained higher numbers of bacteria and increased genera diversity compared with asymptomatic plants [25]. These results suggested that anthracnose restructure endophytic bacterial communities through the selection of certain isolates in the phyloplane of P. cupana.…”
Section: Discussionmentioning
confidence: 94%
“…However, in general, the number and species variation is higher in other plant organs and tissues compared with seeds. In the leaves of guarana obtained from the Amazonas, the numbers varying from 10 4 to 10 5 CFU/g [25]. The isolation of endophytes in seeds is used to examine beneficial microorganisms that might be transferred early to seedlings contributing to promote plant growth, the biological control of pests and other advantages.…”
Section: Discussionmentioning
confidence: 99%